2013
DOI: 10.15288/jsad.2013.74.447
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Reactivity in Two-Year-Old Children Prenatally Exposed to Methamphetamine

Abstract: ABSTRACT. Objective: Until now, the functioning of the hypothalamic-pituitary-adrenal (HPA) axis in children with prenatal methamphetamine exposure (PME) had been unexamined. Previous research indicates that prenatal exposure to stimulant drugs is associated with dose-response alterations in neural growth and connectivity and consequent neurobehavioral defi cits. In addition, children of drug-using parents are at an increased risk for exposure to chronic postnatal stress. In this preliminary study, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, there are few investigations of either short- or long-term effects of early developmental MA exposure, particularly in the context of alterations in the HPA axis function. A 2-year follow up study of children prenatally exposed to MA found that stress-induced cortisol levels were significantly higher in MA-exposed infants (Kirlic et al, 2013 ). Behavioral effects that may be associated with HPA axis alterations in prenatal MA exposed human offspring include altered arousal in infants (Smith et al, 2012 ; Kiblawi et al, 2014 ) and increased emotional reactivity and anxiety/depressed behavior in 3–5 year olds (LaGasse et al, 2012 ; Abar et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few investigations of either short- or long-term effects of early developmental MA exposure, particularly in the context of alterations in the HPA axis function. A 2-year follow up study of children prenatally exposed to MA found that stress-induced cortisol levels were significantly higher in MA-exposed infants (Kirlic et al, 2013 ). Behavioral effects that may be associated with HPA axis alterations in prenatal MA exposed human offspring include altered arousal in infants (Smith et al, 2012 ; Kiblawi et al, 2014 ) and increased emotional reactivity and anxiety/depressed behavior in 3–5 year olds (LaGasse et al, 2012 ; Abar et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this finding of less reactivity in children whose mothers used illicit drugs while pregnant has not been consistently replicated across studies. Specifically, toddlers whose mothers used illicit drugs (mainly cocaine, marijuana, and amphetamine) during pregnancy displayed more negative reactivity during emotionally distressful situations (e.g., “still‐face” procedure, arm restraint task) and were rated as more negatively reactive (e.g., difficult) by their mothers than toddlers whose mothers did not use drugs during pregnancy (e.g., Kirlic et al, 2013; Metosky & Vondra, 1995). Of note, during early childhood, child negative reactivity in response to stressors is typically adaptive and normative at appropriate levels (Razza, Martin, & Brooks‐Gunn, 2012).…”
Section: Evocative Rge In Explaining Child Effects On Parental Negatimentioning
confidence: 99%
“…Prenatal lead (Pb) exposure has been consistently associated with a number of adverse health effects that overlap with cortisol function, including growth [ 5 , 6 ] and altered neurodevelopment [ 7 9 ]. Research on environmental chemical toxicants and their effects on infant or early childhood HPA axis functioning which regulates cortisol excretion [ 10 12 ] remains limited. Studies on lead exposure and cortisol have mixed results, showing an increase or no change in cortisol production in 9 year old children and in occupationally exposed to lead male workers respectively [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%